(untitled) (CIPEEX, 2025)
The present study aims to investigate the exploitation of child labor in rural Brazil, identifying its causes, consequences and the factors that contribute to its persistence. The objective is to understand how this practice affects children’s development and the role of socioeconomic factors in maintaining this problem. The research was conducted through a bibliographical review of previous studies on child labor in Brazil, focusing on rural areas. Data from organizations such as the IBGE (Brazilian Institute of Geography and Statistics) and the ILO (International Labor Organization) were consulted, as well as reports from non-governmental organizations. Furthermore, a qualitative analysis of interviews with experts and rural workers was carried out, exploring the socioeconomic conditions that promote the exploitation of child labor. The results indicate that the exploitation of child labor in rural Brazil is closely related to poverty and lack of access to quality education. Many families, especially in isolated areas, depend economically on their children’s contribution to the family income. The research also revealed that, although there is legislation that prohibits child labor, supervision is insufficient in distant rural areas, which facilitates the continuity of this practice. Children are often exposed to dangerous working conditions, long hours and negative impacts on their health and psychological development. The study concludes that, to effectively combat child labor in rural areas, a set of integrated actions is necessary that involves strengthening public policies to combat poverty, improving access to education and greater supervision by the competent authorities. Raising awareness among families about the harms of child labor and offering viable income alternatives are essential to breaking this cycle. Therefore, it is imperative that the government, non-governmental organizations and civil society work together to eradicate this practice, ensuring the full development of children and respect for their basic rights.